A physically based model for stress sensing using magnetostrictive composites. (December 2015) - Yoffe, Alexander; Weber, Yarden; Shilo, Doron
Abstract: Magnetostrictive composites are of considerable interest for real-time remote force sensing and structural health monitoring. In this paper, we introduce a new procedure for modeling the magnetic field induced by an external load applied on an epoxy-based composite material filled with Terfenol-D particles. This model is based on an assumed sequence of physical processes that occur at the microscopic scale, and it includes both domain switching and magnetization rotation. The modeling procedure is demonstrated on a problem relevant for load sensing applications in which the magnetostrictive composite is subjected to a uniaxial compression. Comparison of the calculated and experimental results strengthens the validity of the assumed sequence of physical processes and provides valuable insights important for application developments.